Meningkatkan Kepercayaan Diri Siswa dan Peran Konselor Sekolah - Yulidar Yulidar; Khairani Khairani (Seminar Konseling 2017, 2017)
This paper begins from the observation of the reality experienced by the majority of students, shows a variety of problems that hamper the development of their potential. The problems which include, incapacity to communicate, hesitant in answering the teacher's questions, reluctant to ask questions, overall mengganbarkan lack of confidence of students. This condition has become a stimulus to study the issue further in the form of a simple discussion include; understanding of self- confidence, individual characteristics that have the confidence, the formation of self-confidence, and the role of the school counselor.